Growth of Online Food Delivery Business in Kathmandu Valley - Mahaseth, Abhishek (Nepalese Journal of Business, 2025)
This study examines the growth of online food delivery business in Kathmandu Valley. Growth of online food businesses is the dependent variable. The selected independent variables are delivery logistics, quality of food, pricing, delivery time, and customer preference. The primary source of data is used to assess the opinions of respondents regarding delivery logistics, quality of food, pricing, delivery time, customer preference, and growth of online food businesses. The study is based on primary data of 127 respondents. To achieve the purpose of the study, a structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of growth of online food delivery business in Kathmandu Valley. The study showed a positive impact of delivery logistics on growth of online food businesses. It indicates that efficient delivery logistics businesses to store and transport their goods to their customers leads to increase in growth of online food business. Similarly, the study showed a positive impact of quality of food on growth of online food businesses. It indicates that higher the quality of food, higher would be the growth of online food business. Likewise, the study also revealed a positive impact of pricing on growth of online food businesses. It indicates that affordable pricing policy leads to increase in growth of online food business. Further, the study observed a positive impact of delivery time on growth of online food businesses. It indicates that fast delivery time leads to increase in growth of online food business. In addition, the study observed a positive impact of customer preference on growth of online food businesses. It indicates that if the customer expectations are meet then which lead to increase in growth of online food business.